Collecting wrappers, labels, and packages to enhance accuracy of food records among children 2–8 years in the Pacific region: Children’s Healthy Living Program (CHL)1 - Yonemori, K.; Ennis, T.; Novotny, R.; Fialkowski, M.; Ettienne, R.; Wilkens, L.; Guerrero, R.; Bersamin, A.; Coleman, P.; Li, F.; Boushey, Carol (Academic Press, 2016)
The aim was to describe differences in dietary outcomes based on the provision of food wrappers, labels or packages (WLP) to complement data from dietary records (DR) among children from the US Affiliated Pacific. The WLP were intended to aid food coding. Since WLP can be associated with ultra-processed foods, one might expect differences in sodium, sugar, and other added ingredients to emerge. Dietary intakes of children (2-8 y) in Alaska, Hawai'i, Commonwealth of the Northern Mariana Islands, and Guam were collected using parent/caregiver completed 2-day DR. Parents were encouraged to collect WLP associated with the child's intake. Trained staff entered data from the DRs including the WLP when available using PacTrac3, a web application. Of the 1868 DRs collected and entered at the time of this report, 498 (27%) included WLP. After adjusting for confounders (sex, age, location, education, food assistance), the DRs with WLP had significantly higher amounts of energy (kcal), total fat, saturated fat, added sugar, and sodium. These results suggest the inclusion of WLP enhanced the dietary intake data. The intake of energy, fat, added sugar and sodium derived from processed foods and foods consumed outside the home was better captured in children who had WLP.Trial registration: NIH clinical trial #NCTT01881373.